Contrastive Study of Brain Activation Regions during Verb Production in Uyghur and Chinese Broca Aphasia Patients after Stroke - ZUHERE Rouzi; MENG Shikai; MA Xiaoting; XI Yanling (康复学报)
ObjectiveBlood oxygenation level dependent-functional magnetic resonance image (Bold-fMRI) was used to compare the brain activation of Uyghur and Chinese broca aphasia patients during verb production task, exploring the neural mechanism of verb production, in order to provide basis for the evaluation and treatment of Uyghur and Chinese broca aphasia patients.MethodsA total of thirty-one patients with broca aphasia who met the inclusion and exclusion criteria were selected, including 15 patients in the Uyghur patient group and 16 patients among the Chinese patient group. Thirty-six healthy volunteers were recruited and matched with the patients in the ethnicity, sex, age and years of education, with 18 in each group. Language function was evaluated by Uyghur and Chinese standard aphasia test. Using Uyghur and Chinese nouns as basic experimental materials, Bold-fMRI data were collected when subjects performed the verb production task. SPM 8.0 software was used for statistical analysis, language and aphasia factors were used for double factor variance analysis to compare the interaction at the whole brain level of the four groups. Simple effect analysis was performed in the brain regions with significant interaction, and the differences in brain activation were compared between the two groups.ResultsIn terms of language functions, there were no significant differences in repetition, naming, listening and understanding, reading, writing scores and BDAE grading between the Uyghur and Chinese patient groups (P>0.05). The four groups showed significant interaction in the activation of bilateral lateral occipital lobe, middle frontal gyrus, precentral gyrus, superior temporal gyrus and fronto-orbital gyrus; there were statistically significant differences in activation intensity of bilateral middle frontal gyrus between the Uyghur healthy group and patient group (P<0.05), but there were no statistically significant differences in activation intensity of precentral gyrus and left lateral occipital lobe (P>0.05). There were statistically significant differences in activation intensity of precentral gyrus and left lateral occipital lobe between the Chinese healthy group and patient group (P<0.05), while there were no statistically significant differences in activation intensity of bilateral middle frontal gyrus (P>0.05). There were no statistically significant differences in simple effect comparison between the Uyghur healthy group and Chinese healthy group, or the Uyghur patient group and Chinese patient group (P>0.05).ConclusionLanguage type and aphasia both affect neural mechanism of brain verb production; the left middle frontal gyrus may play an important role in morphological processing of Uyghur verbs; the precentral gyrus may be involved in phonetic coding output of Chinese.